IMPLEMENTASI KEBIJAKAN LAYANAN ASPIRASI DAN PENGADUAN ONLINE KOTA BANDUNG - Rachmawati, Sinta Yulia; Fajarwati, Arnia (Jurnal Sosial Politik Unla, 2023)
The background of this research is the non-optimal implementation of the Online Aspiration and Complaint Service Policy in Bandung City. The aim of this study is to comprehensively understand, analyze, and describe how the implementation of the Online Aspiration and Complaint Service Policy in the City of Bandung unfolds. The theoretical framework employed in this research is George C. Edward III’s Policy Implementation model as adapted by Subarsono, which comprises four dimensions: Communication, Resources, Disposition, and Bureaucratic Structure. The research formulates propositions for the optimal implementation of the Online Aspiration and Complaint Service Policy at the Department of Communication and Informatics of the City of Bandung based on the factors of Communication, Resources, Disposition, and Bureaucratic Structure. The research methodology employed is qualitative research with a descriptive approach. Data is gathered through literature review, participant observation, in-depth interviews, and documentation. The findings of this research reveal that the implementation of the Online Aspiration and Complaint Service Policy in the City of Bandung is suboptimal due to a lack of public awareness and socialization regarding the LAPOR application, which is the primary reason for the limited knowledge of the public about the application.